Organoleptic Evaluation and Consumer Preferences for Singkil Tea and Kombucha Products (Premna corymbose Rottl. Et Willd) - Teguh Pribadi; Zulfa Zakiyyah; Nurul Anisa; Imam Wijayadi; Masitah Masitah; Eadvin Rosrinda Awang Sari; Ingghrid Ranesti Clarita Hadi; Ayu Indah Rahmawati (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Changes in tea consumption trends present opportunities for the tea industry, especially as alternative raw materials have been tested in recent years to develop tea and kombucha with distinct organoleptic and functional properties. This study evaluates the organoleptic characteristics and consumer preferences for Singkil tea and Singkil kombucha. Methodology: A sensory evaluation was conducted with 30 untrained panelists to assess color, aroma, taste, texture, and overall acceptability using a hedonic scale. Additionally, the alcohol content was measured. Findings: The results of the hedonic test indicated that all treatments fell into category 3 "slightly liked", suggesting an acceptable level of consumer preference. On average, both Singkil tea and Singkil kombucha received an acceptance score of 3, indicating that they were "slightly liked." This suggests their potential as alternative beverages suitable for commercialization. Furthermore, the safety of the product was confirmed, as it contains 0% alcohol, meets halal standards. Contribution: This study concludes that Singkil kombucha has the potential to be a viable alternative beverage for the market, and that it is safe for consumption due to its 0% alcohol content, which complies with halal standards